Penyuluhan Kesehatan Pijat Oksitosin pada Ibu Menyusui di PMB Jamilah Tahun 2024 - Ummy Khairussyifa; Atri Rudtitasari; Asri Fitri Yati; Hearty Efifania Ose Payon; Yolanda Montessori (Jurnal Kabar Masyarakat, 2025)
Optimal growth and development, WHO/UNICEF Global Strategy for Infant and Young Child Feeding recommends 4 important things that must be done, including: giving breast milk to babies immediately within 30 minutes after the baby is born, giving only breast milk or giving exclusive breast milk from birth until the baby is 6 months old, giving MP-ASI from the time the baby is 6 months old to 24 months or more (Yuliarti, 2010). What was found was that there were mothers who were not able to breastfeed their babies directly because breast milk production was little or non-existent. Oxytocin massage has become a therapy that can reduce levels of Adenocorticotropic Hormone (ACTH) and which helps the secretion of hormones and prolactin so that breast milk production runs smoothly. To increase public knowledge, especially breastfeeding mothers, about oxytocin massage, health education can be carried out (Purnama, 2013). The aim of this service is to provide education to breastfeeding mothers about oxytocin massage to help produce and express breast milk so that babies get enough breast milk. The methods used are counseling and demonstration or practice of implementing oxytocin massage. From the community service activities carried out at BPM Jamilah in July 2024 on 31 breastfeeding mothers, we can see significant results regarding the ability of breastfeeding mothers to answer questions asked by the presenters and the willingness of mothers and families to practice oxytocin massage.